THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON BRAND EQUITY AND BRAND LOYALTY WITH BRAND REPUTATION AS A MEDIATING VARIABLE - Yokie Radnan Kristiyono; Michael Fernando Djoni (Faculty of Economics and Business Universitas Pelita Harapan, 2023)
This research aims to analyze the positive influence of Corporate Social Responsibility on Brand Reputation at PT. Astra International Tbk, to analyze the positive influence of Corporate Social Responsibility on Brand Equity at PT. Astra International Tbk, to analyze the positive influence of Corporate Social Responsibility on Brand Loyalty at PT. Astra International Tbk, to analyze the positive influence of Brand Reputation on Brand Equity at PT. Astra International Tbk, to analyze the positive influence of Brand Reputation on Brand Loyalty at PT. Astra International Tbk, to analyze whether Brand Reputation can mediate the influence of Corporate Social Responsibility on Brand Equity at PT. Astra International Tbk, and to analyze whether Brand Reputation can mediate the influence of Corporate Social Responsibility on Brand Loyalty at PT. Astra International Tbk. This research uses a quantitative study approach with data collection through a questionnaire from 210 respondents. The population in this study is consumers of PT. Astra International Tbk who are aware of the company's Corporate Social Responsibility program. The analytical method used in this study is partial least squares (PLS) and the data processing is done using Smart-PLS 3 software.